COMPARISON OF THE VALUES OF EFT (External Fixation Time) IN THE TREATMENT OF LOWER LEG OPEN FRACTURES AND NON-UNIONS WITH THE METHOD OF COMPRESSION-DISTRACTION OSTEOSYNTHESIS BY ILIZAROV - Sheshoski, Ognen; Stojmenski, Slavcho; Atanasov, Nenad; Trpeski, Simon; Miloshevski, Petar (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
Open tibial fractures rank among the most common injuries to long bones, with an annual incidence of 3.4 per 100,000. Complications such as non-unions may arise in 2-10% of these injuries. The Ilizarov method offers a universal opportunity for definitive treatment in both conditions. This retrospective unicentric cohort study aims to assess the value of External Fixation Time (EFT) in patients with open tibial fractures and non-unions treated with compression-distraction osteosynthesis by Ilizarov, followed by a comparative analysis. We evaluated 30 patients treated between 2014 and 2019 for open fractures or non-union of the tibia. The average ages for the two groups were 46 and 50 years, respectively. The latter group had an average of 1.6 prior surgical treatments, with approximately 14 months elapsed since the injury. All subjects examined achieved bone healing. The average EFT values were 160 and 210 days for the treatment of open fractures and non-unions, respectively. There is a statistically significant difference in the EFT values between both groups. 97% of the patients demonstrated satisfactory radiographic results based on the ASAMI scoring system.Treatment with compression-distraction osteosynthesis by Ilizarov proved effective for both open fractures and non-unions of the lower leg. A statistically significant difference exists between the two groups in terms of EFT values representing the duration of treatment. Keywords: open fractures, non-unions, Ilizarov, EFT.